2007
DOI: 10.1177/0163443707078423
|View full text |Cite
|
Sign up to set email alerts
|

Citizens and consumers: discursive debates during and after the Communications Act 2003

Abstract: The regulation of media and communications in the UK has recently been subject to reform resulting in the creation of the Office of Communications (Ofcom). This statutory body, established by an Act of Parliament, is a new, sector-wide regulator, protecting the interests of what has been termed the ‘citizen-consumer’. This article charts the discursive shifts that occurred during the passage of the Communications Act through Parliament and in the initial stages of its implementation to understand how and why t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Doyle and Vick (2005) identify that discussion documents had initially preferred an 'evolutionary approach to regulatory development' (75) building from existing legislation, but the implementation of a 'super-regulator' (Livingstone, Lunt and Miller 2007, 613) presented a significant shift for the government approach to electronic communications. As Livingstone, Lunt and Miller (2007) highlight, this policy shift extended to the complex framing of the wider public as 'citizen-consumers' and a greater tendency towards market regulations and 'competition' principles to ensure that consumer interests were met under the Act. Rather than simply establishing a dual-interest approach to media policy -recognition that individuals interact with media systems as both citizens and consumers in equal measure - Livingstone et al (2007) suggest the somewhat axiomatic positioning of 'citizen' alongside consumer disrupts the function of the former in favour of the latter.…”
Section: Convergence and Policy Renewalmentioning
confidence: 99%
See 1 more Smart Citation
“…Doyle and Vick (2005) identify that discussion documents had initially preferred an 'evolutionary approach to regulatory development' (75) building from existing legislation, but the implementation of a 'super-regulator' (Livingstone, Lunt and Miller 2007, 613) presented a significant shift for the government approach to electronic communications. As Livingstone, Lunt and Miller (2007) highlight, this policy shift extended to the complex framing of the wider public as 'citizen-consumers' and a greater tendency towards market regulations and 'competition' principles to ensure that consumer interests were met under the Act. Rather than simply establishing a dual-interest approach to media policy -recognition that individuals interact with media systems as both citizens and consumers in equal measure - Livingstone et al (2007) suggest the somewhat axiomatic positioning of 'citizen' alongside consumer disrupts the function of the former in favour of the latter.…”
Section: Convergence and Policy Renewalmentioning
confidence: 99%
“…As Livingstone, Lunt and Miller (2007) highlight, this policy shift extended to the complex framing of the wider public as 'citizen-consumers' and a greater tendency towards market regulations and 'competition' principles to ensure that consumer interests were met under the Act. Rather than simply establishing a dual-interest approach to media policy -recognition that individuals interact with media systems as both citizens and consumers in equal measure - Livingstone et al (2007) suggest the somewhat axiomatic positioning of 'citizen' alongside consumer disrupts the function of the former in favour of the latter. In contrast to the strong public service remit of the BBC and its concern with a unified audience, Livingstone et al (2007) argue that:…”
Section: Convergence and Policy Renewalmentioning
confidence: 99%
“…Of course, regulation cannot always be easily quantified. As Livingstone et al (2007) have observed, Ofcom's attempt to act in the 'public interest' has been hampered by the lack of agreement about how the 'public' are defined or the 'interests' that should be pursued. Evidence-driven regulation, in other words, is not as easy to put into practice when there are no precise measures that can be used and interpreted to observe the boundaries of 'public interest'.…”
Section: Challenging 'Light Touch' Orthodoxy: Towards More Evidence-dmentioning
confidence: 99%
“…Each of these differences in assumptions, we would argue, is tied to elements of Canada's distinct political cultures and communications regulatory processes, including the relative industry sizes and corresponding sizes of relevant lobby groups and public affairs consultancies in the two jurisdictions (cf. Livingstone & Lunt, 2007, and Livingstone, Lunt, & Miller, 2007a, 2007b, in the British context, and Raboy 1995a, 1995b, 1995c in the Canadian setting).…”
Section: Policy Ghettosmentioning
confidence: 99%